Lost and Found, or about Henryk Gotlib’s "Polish War-Time Triptych" and its Changing Fate - Gawrońska (Ligocka), Roksana (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English verion. Original issue: “Archiwum Emigracji” 2015, no. 1–2 (22–23) https://apcz.umk.pl/AE/article/view/AE.2015.018